FACTS OF (FINANCIAL) LIFE: POLITICAL POWER AND RE-VISUALIZATION STRATEGIES ON SOCIAL MEDIA - Amit-Danhi, Eedan (AoIR Selected Papers of Internet Research, 2021)
Digital visualizations have seen an exponential rise in use by politicians, candidates and other political actors. Digital visualizations may be informative and engaging as well as potentially, persuasive or misleading when applied by political candidates. However, the ways in which different actors utilize them has yet to receive systematic scholarly attention. Informed by a comprehensive theoretical framework related to political power, digital visualizations and social media campaigns, I performed grounded qualitative content-analysis of all "cost-of-living" visualizations posted to Facebook during the 2015 Israeli election period, by both peripheral and primary political actors. I define two main argumentation strategies (Progress Makers & Hinderers and Re-visualized Economy), reliant on different narrative, visual, and information-oriented choices by different actors. An overview of my findings reveals digital visualizations as a meeting ground between the political power of actors, the rhetorical power of emotionality and the cultural power of numbers. I conclude with a reflection on revisualization as a means of expanding a fourth type of power, discursive power, wherein visualizations are used as an act of resistance by weaker actors against the narrative of reality promoted by stronger actors, relying on the rhetorical affordances of the digital political visualization genre toincrease their rhetorical power. Digital visualizations thus offer a uniquely agile tool for political actors of all types to utilize in gaining discursive power in the competition over election narratives in the digital arena of social media.